AIM1‐dependent high basal salicylic acid accumulation modulates stomatal aperture in rice. Issue 4 (18th March 2023) - Xu, Lei; Zhao, Hongyu; Wang, Junbin; Wang, Xuming; Jia, Xianqing; Wang, Long; Xu, Zhuang; Li, Ruili; Jiang, Kun; Chen, Zhixiang; Luo, Jie; Xie, Xiaodong; et al.
Summary: The basal levels of salicylic acid (SA) vary dramatically among plant species. In the shoot, for example, rice contains almost 100 times higher SA levels than Arabidopsis. Despite its high basal levels, neither the biosynthetic pathway nor the biological functions of SA are well understood in rice. Combining with metabolite analysis, physiological, and genetic approaches, we found that the synthesis of basal SA in rice shoot is dependent on OsAIM1, which encodes a beta‐oxidation enzyme in the phenylalanine ammonia‐lyase (PAL) pathway. Compromised SA accumulation in the Osaim1 mutant led to a lower shoot temperature than wild‐type plants. However, this shoot temperature defect resulted from increased transpiration due to elevated steady‐state stomatal aperture in the mutant. Furthermore, the high basal SA level is required for sustained expression of OsWRKY45 to modulate the steady‐state stomatal aperture and shoot temperature in rice. Taken together, these results provide the direct genetic evidence for the critical role of the PAL pathway in the biosynthesis of high basal level SA in rice, which plays an important role in the regulation of steady‐state stomatal aperture to promote fitness under stress conditions.